As Physics
 0
 0
 7
 0
 0

 0
 0
posted by bobpursley

 0
 0
posted by cylinder
Respond to this Question
Similar Questions

math
Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8
asked by Anonymous on October 25, 2018 
English
Procedure : Group Activity Looking at the picture on the left, let's play the guessing game. I have some pictures. Look at this picture. What is he doing? Guess what he is doing and say like this: He is running. I think he is
asked by John on June 9, 2008 
ALGEBRA HELP
When solving the equation, what property was used to go from step 3 to step 4? Step 1: (2x+3= x18 Step 2: 2x3=x18 Step 3: 3=3x18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE
asked by cv on October 22, 2013 
chemistry
What is the percent ionization of a 1.38 mol/L weak acid if its Ka = 2.7 x 106? Answer to two (2) decimal places. I know what steps to use but have difficulty applying them to the quesiton Can someone please complete the question
asked by Anna on April 19, 2008 
Physics
An arrow is shot straight up from the edge of a cliff with an initial velocity of 50 ft/s. Answer the following questions using English units. The acceleration due to gravity has a magnitude of 32.2 ft/s. A. Find the time to reach
asked by Maggie on August 22, 2016 
Chemistry
In a chain mechanism, a reaction in which two free radicals combine to form a stable molecule would be called the A) initiation step B) termination step C) propagation step D) inhibition step E) branching step
asked by Haley on April 8, 2015 
Algebra help
f(x)=x^34x^2x+4 How do I find the xintercept for this? This is from my book: step 1: 0=x^34x^2x+4 step 2: 0=x^2(x4)+(1)(x4) step 3: 0=(x^21)(x4) I know how to solve once I get to step 3, but in step 2, I don't know what
asked by Claure on June 16, 2009 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,
asked by oscar on September 4, 2015 
aps
There are 26 step on flpor at the time saad comes down two step imad step up one step When will tyey meet at what step?
asked by sayed on January 24, 2017 
Math
In which step is the error? Step 1: Let x = 1 and y = 1. Step 2: By substitution xy = y^2. Step 3: Multiplying both sides by 1, xy= y^2. Step 4: Adding x^2 to both sides, x^2xy=x^2y^2. Step 5: Factoring, x(xy)=(x+y)(xy).
asked by Hannah on February 1, 2016